An Advance Node Pairing Protocol for Wireless Sensor Networks - Yadav, Amit; Kohli, Narendra; Yadav, Anil (International Journal of Integrated Engineering, 2021)
In the recent developments in the communication system, the role of Wireless sensor network (WSN) is remarkable. In WSN information is collected using sensors and then it is transmitted to sink node. For this collection and transmission, the nodes need power back up and hence the power back up of nodes is one of the most crucial factor which will influence the proper functioning of WSN. This is the reason behind why we focus on the less consumption of the power by the nodes while making any WSN algorithm. This paper presents a node pairing protocol along with clustering of nodes. Overall, field in which sensor node are deployed is divided into zones and in zone 1 simple clustering based mechanism is used for data transfer to BS, while in zone 2, node pairing concept is used, and in a round only one node remain active while other remains in sleep mode thus energy saving is ensured. Simulations results show that the proposed protocol improve stability period 142%, 85.37%, 100.4%, 69.8% 35.5% and 72.43% the improved network lifetime of 55%, 128.9%, and 113.2% , 96.42% 27.38% and 40.93% as compared to LEACH, DEEC, DDEEC, MAHEE, S-SEP and EECP-EI respectively.